1993
DOI: 10.4141/cjss93-004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and biochemical changes induced by rotation and tillage in a soil under barley production

Abstract: and three tillage treatments (moldboard plowing (MP), chisel plowing (CP) and no-tillage (NT)) were compared in a split-plot design. Total organic C was affected by the tillage treatments but not by the rotations. In the topsoil layer (0-7.5 cm), NT and CP treatments had C,contents 20% higher than the MP treatment. In the same soil layer, MBC averaged 300 mg C kg-' in the MP treatrnent and up to 600 mg C kg-l in the NT soil. Hot-water-extractable and acid-hydrolyzable carbohydrates were on average 4O% greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
1
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 1 publication
6
87
1
6
Order By: Relevance
“…Soil structural stability was determined on soil samples obtained from the 0-to 10-and 10-to 20-cm soil depths only using a wet-sieving method (Angers and Mehuys 1993). Duplicate air-dried soil sub-samples (30 g) were placed on a nest of sieves (2.00, 1.00, 0.50, and 0.25 mm).…”
Section: Crop and Soil Sampling And Analysismentioning
confidence: 99%
“…Soil structural stability was determined on soil samples obtained from the 0-to 10-and 10-to 20-cm soil depths only using a wet-sieving method (Angers and Mehuys 1993). Duplicate air-dried soil sub-samples (30 g) were placed on a nest of sieves (2.00, 1.00, 0.50, and 0.25 mm).…”
Section: Crop and Soil Sampling And Analysismentioning
confidence: 99%
“…Addition of LHM to soil for several years may reduce its total C content, partly due to microbial oxidation of the native organic matter to support high bacterial growth (de Laval 1975). This oxidation of organic C can particularly be observed when crops do not leave enough residues to ensure the mainte-nance of soil C levels such as is the case of silage corn (Angers and Carter 1996). On the other hand, its high NH 4 + -N content could rapidly stimulate its nitrification under favorable soil aerobic conditions (Morvan et al 1996).…”
mentioning
confidence: 99%
“…Monoculture corn is well-known to cause the physical degradation of soil (Tabi et al 1990), which may impair soil biological properties (Angers et al 1993). Soil conservation practices, such as manure addition, crop rotations and reduction of tillage intensity, have a profound influence on the size and activity of the soil microbial biomass (Schnürer et al 1985;Simard et al 1994).…”
mentioning
confidence: 99%
“…In both soils the carbohydrate C content was lowest in the 4.0-8.0 mm fraction. Several longterm studies have shown that rotation with legumes can increase the amount of carbohydrates in soil (6,10,18). Soil carbohydrates were strongly influenced by soil management systems, including amendments with bark compost or leaf litter (19).…”
Section: Carbohydrates and Soil Aggregates 629mentioning
confidence: 99%
“…They consist primarily of extracellular carbohydrates and are produced by bacteria, fungi, and plants. Many studies showed that bonding of carbohydrates were the main aggregating agent (10,24). …”
Section: Carbohydrates and Soil Aggregates 629mentioning
confidence: 99%